(untitled) (Texas Journal of Medical Science, 2025)
Early-stage chronic kidney disease (CKD) represents a critical opportunity for intervention aimed at delaying disease progression and reducing long-term complications. Although pharmacological treatment remains essential, increasing evidence indicates that dietary management plays a central role in modulating the pathophysiological mechanisms underlying renal decline. This study reviews and analyzes current evidence on the effects of targeted dietary interventions — including moderate protein restriction, sodium reduction, phosphorus control, and plant-forward dietary patterns — on renal outcomes in patients with CKD stages 1–3. The findings suggest that individualized nutritional strategies can slow the decline in glomerular filtration rate, reduce proteinuria, improve metabolic and inflammatory profiles, and enhance cardiovascular risk management. Integrating dietary therapy into early CKD care may therefore offer a safe, cost-effective, and sustainable approach to improving patient outcomes